p53 Gene Codon 72 Polymorphisms among Cervical Carcinoma Patients - Rustham Basyar; Agustria Z Saleh; Irawan Sastradinata; Yuwono Yuwono (Indonesian Journal of Obstetrics and Gynecology, 2015)
Objective: To identify the association between p53 gene codon 72 polymorphism and cervical carcinoma. Method: An analytic observational study with case-control design, from November 2013 until March 2014 in the Department of Obstetrics and Gynecology and Microbiology Laboratory Faculty of Medicine, Sriwijaya University, Dr. Moh. Hoesin Hospital Palembang. Result: In total there are 100 samples analyzed consisting of 50 subjects and 50 control groups. Genotype distribution in subject group are 54% Arg/Arg, 42% Pro/Arg and 4% Pro/Pro, and in control group are 36% Arg/Arg, 46% Pro/Arg and 18% Pro/Pro. Arg/Arg genotype is at risk of cervical carcinoma 6.7 times higher compared with Pro/Pro genotype (p=0.013; OR 6.75; 95% CI 1.34-34.94). Arg allele in the p53 gene codon 72 increase the risk of cervical carcinoma 2.6 times more than Pro allele. Conclusion: Proline mutation to Arginine in gene p53 P72R is one of the risk factor for cervical carcinoma. Keywords: arginine, cervical carcinoma, gene p53 codon 72, polymorphism, proline